2021
DOI: 10.1038/s42004-021-00505-2
|View full text |Cite
|
Sign up to set email alerts
|

One-pot catalytic synthesis of urea derivatives from alkyl ammonium carbamates using low concentrations of CO2

Abstract: To reduce anthropogenic carbon dioxide (CO2) emissions, it is desirable to develop reactions that can efficiently convert low concentrations of CO2, present in exhaust gases and ambient air, into industrially important chemicals, without involving any expensive separation, concentration, compression, and purification processes. Here, we present an efficient method for synthesizing urea derivatives from alkyl ammonium carbamates. The carbamates can be easily obtained from low concentrations of CO2 as present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…Koizumi and co-workers reported that CeO 2 (<25 nm) was active for the synthesis of 1 from EDA-CA, but the activity was low (yield 29%, 443 K). 29 In contrast, in our case, by using nano-CeO 2 (84 m 2 /g, 9 nm), the yield reached 83% at a low temperature of 413 K, and such a lower reaction temperature is beneficial for the suppression of EDA-CA decomposition. These results mean that our CeO 2 catalyst is quite active for the reaction.…”
Section: ■ Results and Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Koizumi and co-workers reported that CeO 2 (<25 nm) was active for the synthesis of 1 from EDA-CA, but the activity was low (yield 29%, 443 K). 29 In contrast, in our case, by using nano-CeO 2 (84 m 2 /g, 9 nm), the yield reached 83% at a low temperature of 413 K, and such a lower reaction temperature is beneficial for the suppression of EDA-CA decomposition. These results mean that our CeO 2 catalyst is quite active for the reaction.…”
Section: ■ Results and Discussioncontrasting
confidence: 60%
“…The highest yield of 83% was obtained at 413 K with a proper amount of the 2-propanol solvent (15 mL). The formation rate was calculated from the slope of the time course at a low conversion level (<40%, Figure S5 and Table S6) to be 0.60 h –1 at 413 K. The value is a little higher than that with the reported homogeneous catalyst system of Cp 2 Ti­(OTf) 2 (0.47 h –1 ) at 433 K despite the 20 K lower reaction temperature. Koizumi and co-workers reported that CeO 2 (<25 nm) was active for the synthesis of 1 from EDA-CA, but the activity was low (yield 29%, 443 K) .…”
Section: Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several organic bases, including bicyclic guanidine, have been explored for cyclic urea synthesis . The homogeneous titanium complex has also been found effective for synthesizing cyclic urea from alkyl ammonium carbamate . Several heterogeneous catalysts, including Au decorated in the polymer matrix, metal oxides (including CeO 2 ), silica-based catalysts, and MOF, have been reported for this reaction. Sn and Ni metal complexes have been utilized for carbamate synthesis. Moreover, CeO 2 has also been explored for carbamate synthesis …”
Section: Introductionmentioning
confidence: 99%